2003
DOI: 10.1177/13540688030092003
|View full text |Cite
|
Sign up to set email alerts
|

Species of Political Parties

Abstract: A B S T R A C TWhile the literature already includes a large number of party typologies, they are increasingly incapable of capturing the great diversity of party types that have emerged worldwide in recent decades, largely because most typologies were based upon West European parties as they existed in the late nineteenth through mid-twentieth centuries. Some new party types have been advanced, but in an ad hoc manner and on the basis of widely varying and often inconsistent criteria. This article is an effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
20

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(73 citation statements)
references
References 30 publications
0
53
0
20
Order By: Relevance
“…Gibson (2009) goes further to suggest that new 'e-campaigning' strategies and technologies have the potential to challenge existing party and political elites. In a similar way, Gunther and Diamond (2003) and Kitschelt (2006), in describing movement parties, have suggested that such parties may change organizational form but do not describe how that happens, or what impact is required, other than 'electoral shock', a concept also utilized by Gibson and Rommele (2009). Such an approach does not appear to consider that parties such as the Australian Greens may in fact no longer be a party solely focused on intra-party democracy (see Villalba 2008), but that the structures that once facilitated that now act as an impediment to vote-seeking.…”
Section: Australian Parties Online Campaigningmentioning
confidence: 82%
“…Gibson (2009) goes further to suggest that new 'e-campaigning' strategies and technologies have the potential to challenge existing party and political elites. In a similar way, Gunther and Diamond (2003) and Kitschelt (2006), in describing movement parties, have suggested that such parties may change organizational form but do not describe how that happens, or what impact is required, other than 'electoral shock', a concept also utilized by Gibson and Rommele (2009). Such an approach does not appear to consider that parties such as the Australian Greens may in fact no longer be a party solely focused on intra-party democracy (see Villalba 2008), but that the structures that once facilitated that now act as an impediment to vote-seeking.…”
Section: Australian Parties Online Campaigningmentioning
confidence: 82%
“…"Lo que es con Uribe, es conmigo" es otra fórmula mágica y política, que cumple con la función de simbolizar y sintetizar la cosmovisión del colectivo y de ahí pasar a su proceso de amplificación (Benford y Snow, 2000). Este lema recoge el carácter personalista del partido (Gunther y Diamond, 2003y Panebianco, 1990, es decir, reafirma el carisma personal del líder como componente indispensable de la organización, al llamar a profesionales de la política y profanos a cerrar filas a su alrededor. Así mismo, reafirma la desconfianza en el poder judicial y la idea de la "persecución política".…”
Section: Figura7unclassified
“…Como dato que atraviesa toda la reflexión, no se puede omitir que el Centro Democrático tiene los rasgos de un partido personalista y carismático: buena parte de su atractivo electoral se basa en el carisma personal del líder, concebido como indispensable para resolver los problemas del país (Gunther y Diamond, 2003y Panebianco, 1990. El carisma de Uribe emergió en una situación de crisis en la economía y el orden público y durante sus años de gobierno este agente acumuló un capital político de tipo heroico o personal profético (Meichsner, 2007).…”
Section: Comentarios Finales: Conclusiones Y Nuevas Preguntasunclassified
“…Na realidade, os estudos comparativos deram contribuições muito limita-das para a compreensão de quais fatores afetam a natureza da organização partidária de cada país, e sobretudo para a avaliação do impacto específico produzido pelos sistemas eleitorais (Gallaguer, 2005). A variedade de tipos de partidos no interior de um mesmo país mostra queos efeitos dos sistemas eleitorais devem ser matizados (Gunther e Diamond, 2003). No Brasil, por exemplo, mesmo com um sistema altamente centrado no candidato, um partido (PT) conseguiu desenvolver mecanismos de reforço da reputação partidária (Samuels, 1999;Leal, 2005).…”
Section: Efeitos Sobre Os Partidosunclassified